Starting with 3x^2-7x+12=0, we divide all four terms by 3, resulting in the following factored form:
3(x^2-[7/3]x+4)=0.
Since 3 cannot equal 0, we can focus on the following:
x^2 - 7/4 x =-4
This completes the assignment (describe Joe's steps up to this point).
If you wish to go further:
Next, take HALF of the coefficient of x and square your result:
(-7/[4][2])^2 = 49/64
Add this to both sides of x^2 - 7/4 x =-4: x^2 - 7/4x + 49/64 =-4+49/64
Rewrite the left side as (x-7/8)^2 and the right side as 49/64 - 256/64
Simplify the right side by combining these terms: -207/64
Then x-7/8 = plus or minus (1/8)sqrt(-207)
Next, x = 7/8 plus or minus (1/8)*i*√207, or
7 plus or minus i*√207
x = ----------------------------------
8